Determination of Foreign Direct Investment (FDI) in the Manufacturing Sectors in Malaysia - Wong Hock Tsen (Current Topics on Business, Economics and Finance Vol. 1, 2023)
The present study examines the foreign direct investment (FDI) determinants in the main manufacturing sectors and the impact of FDI on economic growth in Malaysia. Moreover, this study examines the link between FDI and real national income. The vector error correction model (VECM) is used to estimate FDI determinants and the link between FDI and real national income.Foreign direct investment (FDI) is a vital driver for economic growth in a country. Hence, FDI determinants should be identified in order to promote FDI. FDI could stimulate economic growth and economic growth could attract FDI. A variety of policies shall be implemented to promote FDI as FDI determinants are not the same for all subsectors of the manufacturing sector in Malaysia. Promoting FDI can be more challenging in globalisation of the world economy today than before. The government shall promote FDI that encourages the growth of the domestic industry. Many manufacturing sectors are found to be significantly influenced by autocracy and polity. It has been discovered that inflation has a negative impact on FDI in the transport equipment sector. It is discovered that the Asian financial crisis of 1997–1998 had a significant impact on FDI in the chemical and chemical products sector as well as the petroleum products sector. These findings reveal that FDI determinants are not exactly the same for all the manufacturing sectors. Therefore, FDI would be attracted through a variety of policies. The sectors of basic metal products, chemicals, and chemical products are found to be Granger causes of real national income, whereas the sector of petroleum products is found to be Granger cause of FDI. These findings show a connection between FDI and economic expansion. Malaysia’s economy can continue to grow thanks to FDI. FDI is essential for economic expansion.